2017
DOI: 10.1183/13993003.01818-2016
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea as a cause of nocturnal nondipping blood pressure: recent evidence regarding clinical importance and underlying mechanisms

Abstract: Obstructive sleep apnoea (OSA) is highly prevalent, with recent general population studies indicating that up to 50% of males and 23% of females have moderate or severe sleep disordered breathing (SDB) based on an apnoea-hypopnoea index (AHI) of >15 events·h -1 [1, 2]. OSA is recognised as an independent risk factor for systemic hypertension [3] and a nondipping nocturnal blood pressure profile is particularly likely in patients with OSA [4], even in the absence of significant hypertension. Furthermore, hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 41 publications
(48 reference statements)
1
42
0
3
Order By: Relevance
“…Studies have consistently demonstrated elevated blood pressure (BP), a well-known risk factor for cardiovascular and cerebrovascular adverse outcomes, in children4 6 8 9 and adults10 with OSA. Non-dipping of nocturnal BP (reduction of nocturnal BP <10% from daytime level) has also been demonstrated in both adults and children with OSA 11–18. The phenomenon of non-dipping in nocturnal BP precedes the development of hypertension in normotensive individuals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have consistently demonstrated elevated blood pressure (BP), a well-known risk factor for cardiovascular and cerebrovascular adverse outcomes, in children4 6 8 9 and adults10 with OSA. Non-dipping of nocturnal BP (reduction of nocturnal BP <10% from daytime level) has also been demonstrated in both adults and children with OSA 11–18. The phenomenon of non-dipping in nocturnal BP precedes the development of hypertension in normotensive individuals.…”
Section: Introductionmentioning
confidence: 98%
“…The phenomenon of non-dipping in nocturnal BP precedes the development of hypertension in normotensive individuals. For patients with hypertension, non-dipping is associated with increased target organ damage and worse cardiovascular prognosis 11. Therefore, prevention of BP abnormalities and non-dipping is important to reduce the risk of developing cardiovascular adverse events 19.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the up‐regulation of the renin‐angiotensin‐aldosterone and atrial natriuretic peptide systems in response to raised renin levels and intrapleural pressure swings promotes the body fluid redistribution . Crucially, over time, these autonomic and neurohumoral derangements perpetuate beyond the offending events and persist into the daytime, resulting in a disturbance of the overall circadian BP rhythm and an increase in short‐ and long‐term BPV . In this respect, there is accruing evidence that not only high absolute BP levels but even their fluctuations are closely related to the development and progression of organ damage by promoting arterial remodelling, microvascular damage, hemodynamic instability, and vascular reactivity impairment .…”
Section: From Pathophysiology To Clinical Practice: Implications and mentioning
confidence: 99%
“…OSA may exert marked adverse effects on BP homeostasis through several hemodynamic and chemo‐mediated mechanisms, mainly triggered by the occurrence of repeated episodes of apnoea and hypoxia during sleep leading to intermittent bouts of acute BP changes during nocturnal arousals, with increases in nocturnal systolic BP up to 20‐30 mm Hg within few minutes. The mechanisms underlying the development of hypertension and paradoxical BP increase during sleep include sustained sympathetic over‐activation, endothelial dysfunction, low‐grade inflammation, and progressive increase in arterial stiffness …”
mentioning
confidence: 99%